Die Germania - Tacitus, Cornelius, 56-117 (Salt Lake City, UT : Project Gutenberg, 2012)
"Die Germania" by Cornelius Tacitus is an ethnographic work written around 98 CE about the Germanic peoples. This short text describes the geography of Germania and the customs of its inhabitants, from the Rhine to the Vistula. Tacitus portrays the Germans as hardy, uncorrupted, and fiercely free, praising their family values and courage while noting their weaknesses, including laziness and excessive drinking. The work examines their warfare, religion, governance, and daily life, offering a Roman perspective on these northern neighbors. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Germania_(book) Wikipedia page about this book: https://de.wikipedia.org/wiki/Germania_(Tacitus)
Release date is 2012-04-29
Keywords: Germanic peoples -- Early works to 1800